Male and female violence in popular media - Giomi, Elisa (Library of gender and popular culture, 2023)
"Elisa Giomi and Sveva Magaraggia propose that men engage in violent conduct at a higher rate than women because they are socially and culturally 'programmed' to do so. Popular culture representations play a crucial role in this process: TV series, films, pop music and videos, advertising commercials and tabloids all tend to 'normalise' violence against women as an allegedly natural inclination of males. Violent women, on the other hand, are believed to transgress both criminal and 'natural' laws, according to which they are supposed to give life, not death. By examining popular culture's depiction of men and women in their opposite, yet complementary, roles of perpetrators and victims, the authors show unexplored interconnections, namely that gender 'does' violence and violence 'does' gender. Empirical evidence is presented drawing on the following case studies: - male violence in contemporary Italian pop music - female violence in crime TV series including The Killing (Denmark, 2007-2012),The Fall (UK, 2013-2016) and True Detective (USA, 2015) - the use and abuse of gendered violence in Italian and international advertising images such as billboards and posters - male and female intimate partner violence in factual entertainment (Who the (bleep) Did I Marry? (Investigation Discovery, 2010-2015))"--